2022
DOI: 10.1038/s41467-022-34728-1
|View full text |Cite
|
Sign up to set email alerts
|

Durability and cross-reactivity of immune responses induced by a plant-based virus-like particle vaccine for COVID-19

Abstract: As the SARS-CoV-2 pandemic evolves, vaccine evaluation needs to include consideration of both durability and cross-reactivity. This report expands on previously reported results from a Phase 1 trial of an AS03-adjuvanted, plant-based coronavirus-like particle (CoVLP) displaying the spike (S) glycoprotein of the ancestral SARS-CoV-2 virus in healthy adults (NCT04450004). Humoral and cellular responses against the ancestral strain were evaluated 6 months post-second dose (D201) as secondary outcomes. Independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…However, in this study, we found that the decay patterns of the NAb responses after the peaking following the boosting with aerosolized Ad5-nCoV within 12 months were similar to that following the CoronaVac boosting. Furthermore, this decline of NAb responses was obvious within the first 6 months, and much slower after that, which is consistent with that observed in individuals after receiving other vectored based or virus-like particle COVID-19 vaccines [ 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, in this study, we found that the decay patterns of the NAb responses after the peaking following the boosting with aerosolized Ad5-nCoV within 12 months were similar to that following the CoronaVac boosting. Furthermore, this decline of NAb responses was obvious within the first 6 months, and much slower after that, which is consistent with that observed in individuals after receiving other vectored based or virus-like particle COVID-19 vaccines [ 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…In the follow-up phase, the booster administration with S-268019-b elicited a durable neutralizing antibody response in both groups through the end of the study. Considering that the neutralizing antibodies tend to wane in 6–8 months following administration of the second dose for multiple vaccine types in previously published studies, booster application within that time frame could ensure maintenance of protective immunity 24 , 25 . Indeed, the fact that the neutralizing antibody titer following the booster dose was higher than that after the second dose suggests that immune system was adequately primed with two initial doses to mount the response in both treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are four COVID-19 vaccines that have been authorized by the Food and Drug Administration (FDA) in the US, including Pfizer-BioNTech, Moderna, Johnson & Johnson’s Janssen, and the most recently approved Novavax, with notable effectiveness [ 81 ]. Some new vaccines are also under development, such as the plant-based virus-like particle (CoVLP) vaccine by adjuvanting the purified modified SARS-CoV-2 spike protein expressed in Nicotiana benthamiana with AS03 adjuvant, which has demonstrated notable cross-reactivity against different SARS-CoV-2 variants [ 82 ]. However, with the everchanging genomic information of SARS-CoV-2 and the waning of immunity, breakthrough infections of SARS-CoV-2 have occurred in many cases in vaccinated people [ 83 ].…”
Section: Antiviral Activity Against Sars-cov-2 In Marine Resourcesmentioning
confidence: 99%